The Text–Culture–Living Hadith Model: An Anthropologically Informed Framework for Hadith Contextualization - Widad, Nazilatul; Razi, Fahrur (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2026)
Hadith contextualization requires a method that preserves textual authority while accounting for the historical, cultural, and social conditions relevant to interpretation. Existing studies have examined contextual criticism, anthropological approaches, and living hadith, but these components are not always organized into an explicit analytical sequence with clearly differentiated evidentiary functions. This article formulates the Text–Culture–Living Hadith model as an anthropologically informed framework for hadith contextualization. It employs qualitative library research, content analysis, and conceptual synthesis of hadith sources, methodological scholarship, anthropological studies of Muslim practice, and living hadith research. The framework comprises seven stages: textual identification, attributed evaluation of hadith status, examination of asbab al-wurud and related reports, sociohistorical and cultural analysis, analysis of normative purpose and cultural form, examination of documented reception, and contemporary contextualization. Its application to the report “Whoever has hair should honor it” identifies the source as Sunan Abi Dawud, hadith 4163, and distinguishes it from the related report concerning disheveled hair in hadith 4062. The analysis shows that textual evidence, historical inference, social reception, and contemporary interpretation must be treated as related but non-equivalent forms of evidence. The model contributes a transparent procedural framework for connecting hadith criticism with cultural and reception analysis. It remains a conceptual proposal whose empirical usefulness requires testing through clearly defined textual corpora and field-based studies of Muslim reception.